PENGARUH KOMITMEN ORGANISASI DAN SPIRITUALITAS DI TEMPAT KERJA TERHADAP KINERJA KARYAWAN PERUM BULOG DIVISI REGIONAL KALIMANTAN SELATAN KOTA BANJARMASIN - Annisa Ratu Mulianti; Hastin Umi Anisah; Tinik Sugiati (Universitas Lambung Mangkurat, 2015)
This study aims to determine the effect of partial and simultaneous organizational commitment and spirituality in the workplace on employee performance in Public Corporation BULOG Regional Division South Kalimantan in Banjarmasin City. The research method uses a quantitative approach to the study sample size of 34 employees of Public Corporation BULOG Regional Division South Kalimantan in Banjarmasin City tested using multiple regression analysis with software Statistics Programme for Service Solutions (SPSS) version 20.0. The study, of 34 permanent employees who work in Public Corporation BULOG Division South Kalimantan Banjarmasin, found that organizational commitment and significant positive effect on employee performance. The findings further, that spirituality in the workplace positive and significant impact on employee performance. Simultaneously, organizational commitment and spirituality in the workplace positive and significant impact on employee performance. Based on the results of this study concluded that organizational commitment and spirituality in the workplace is able to address concerns about the performance of employees in Public Corporation Bulog Regional Division South Kalimantan Banjarmasin. Implications of the study is expected to be a positive contribution to improving employee performance and the performance of Public Corporation BULOG Regional Division South Kalimantan in Banjarmasin City and future research.